2021
DOI: 10.1097/fm9.0000000000000091
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Microbiome During Pregnancy

Abstract: Gut microbiota is symbiotic and interdependent with human body. Intestinal probiotics are colonized in the human gastrointestinal tract, which can improve the host intestinal microenvironment and enhance the intestinal function and immune function of the human body. A small number of opportunistic pathogens exist in the intestinal tract. Once the number of pathogens exceeds the threshold of intestinal tolerance, the intestinal micro-ecological balance can be destroyed, and various diseases may thus develop. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…Intestinal probiotics can improve the host's intestinal microenvironment, helping the body improve its intestinal and immune functions. Probiotics can control pregnancy weight gain and reduce complications of pregnancy by inducing changes in the intestinal microbiome during pregnancy [29]. Nordqvist et al [30] found that the consumption of specific probiotics by pregnant women can significantly reduce the incidence of premature birth in early pregnancy and significantly reduce the incidence of PE in late pregnancy.…”
Section: Changes In Community Structure and Compositionmentioning
confidence: 99%
“…Intestinal probiotics can improve the host's intestinal microenvironment, helping the body improve its intestinal and immune functions. Probiotics can control pregnancy weight gain and reduce complications of pregnancy by inducing changes in the intestinal microbiome during pregnancy [29]. Nordqvist et al [30] found that the consumption of specific probiotics by pregnant women can significantly reduce the incidence of premature birth in early pregnancy and significantly reduce the incidence of PE in late pregnancy.…”
Section: Changes In Community Structure and Compositionmentioning
confidence: 99%
“…Some researchers have concluded that these changes are temporary and of no significance ( DiGiulio et al., 2015 ; Yang et al., 2020 ), whereas others have found that insertion of human gut microbes from the third trimester into mice leads to weight gain and more pronounced low-grade inflammation ( Turjeman et al., 2021 ). Furthermore, all alterations in the gut microbiome directly influence maternal metabolism ( Paul et al., 2018 ), which, in turn, impacts the development and growth of fetal organs ( Jiang et al., 2021 ).…”
Section: Changes In Microbiome Associated With Pregnancymentioning
confidence: 99%
“…The maternal and infant gut microbiome, although located in the gastrointestinal tract, are related to health and well-being of the maternal and infant dyad. During gestation, the maternal gut microbiome is thought to produce metabolites with the potential to affect the pregnancy and maturation of fetal tissues and systems ( Jiang et al, 2023 ). Short-chain fatty acids produced by the gut microbiome are widely recognized for their influence on systemic physiology and have been shown to affect maternal weight gain, glucose metabolism, hormone homeostasis, and blood pressure ( Edwards et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%